The dynamic interplay of dietary acid pH and concentration during early-stage human enamel and dentine erosion - Pattem, J.; Field, J.; Waterhouse, P. J.; German, M. J. (Frontiers in Dental Medicine, 2022)
Dental erosion continues to be a significant global health concern affecting nearly 30% of adults world-wide. With increasing soft drink consumption predominantly driving its prevalence, strategies for prevention and control are often implemented when erosion is severe, or rates are high in the populace. While factors affecting dental erosion such as pH on enamel has received much attention, the effect of dietary acid concentration when factored out to a commercially available pH has yet to be determined. Furthermore, understanding these effects on dentine, which is known to be more susceptible to erosion than enamel can unravel structure property relationships between acid characteristics and hard tissue types. This study aimed to develop structure-property relationships between dietary acid concentration, and pH, on the nano-textural and nano-mechanical properties of human enamel and dentine during short-term simulated drinking. To achieve this, a novel sample preparation methodology and analysis approach was developed by applying atomic force microscopy (AFM) in quantitative imaging mode. This enabled simultaneous measurement of enamel and dentine morphology and mechanical properties. Flow-cells were used to simulate drinking, exposing polished and smear layer free human enamel and dentine to 30 s repeated cycles of unbuffered citric acid 6% (pH = 1.88) and 1% (w/v) (pH = 2.55) and commercially available buffered pH = 3.8 states, for up to 180 s. The same 50 µm x 50 µm area of specimen morphology was analysed using in-house developed nanotextural analysis using the bearing area curve (BAC) with a focus on roughness (Ra), normalised peak (PA) and valley areas (VA). Mechanical properties were simultaneously measured for stiffness (N/m) after each 30s. While all studies agree pH is a major factor in the erosion of enamel, here its dominance over the treatment time varied, with concentration surpassing the importance of pH after initial acid contact. Conversely, dentine erosion showed concentration-dependent changes in morpho-mechanical properties only. These results not only highlight the dynamic process of erosion, but how the interplay between acid characteristics and dental tissue type impact the progression of very early-stage erosion.